Inequality and household finance during the consumer age - Barry Z. Cynamon; Steven M. Fazzari (Levy Economics Institute of Bard College, 2013)
One might expect that rising US income inequality would reduce demand growth and create a drag on the economy because higher-income groups spend a smaller share of income. But during a quarter century of rising inequality, US growth and employment were reasonably strong, by historical standards, until the Great Recession. This paper analyzes this paradox by disaggregating household spending, income, saving, and debt between the bottom 95 percent and top 5 percent of the income distribution. We find that the top 5 percent did indeed spend a smaller share of income, but demand drag did not occur because the spending share of the bottom 95 percent rose, accompanied by a historic increase in borrowing. The unsustainable rise in household leverage concentrated in the bottom 95 percent ultimately spawned the Great Recession. The demand drag of rising inequality could be one explanation for the stagnant recovery in the recession's aftermath.
Keywords: D12; D31; E21; 330; consumption; saving; inequality; aggregate demand